Emotional Intelligence, Psychological Needs Satisfaction, and Stress of Teachers Amidst Pandemic - Jacquelyn Rose A. Fajilagutan (Future Science / FSH-PH Publications, 2026)
The COVID-19 pandemic posed unprecedented challenges to the education sector, placing elementary teachers under sustained psychological and emotional strain due to increased workload, shifting instructional demands, and limited support systems. This study examined the relationships among emotional intelligence, psychological need satisfaction, and stress among elementary teachers during the COVID-19 pandemic as a basis for proposing a school-based mental health program. Employing a convergent parallel mixed-methods design, quantitative and qualitative data were collected concurrently and integrated during interpretation. Quantitative data were gathered from 253 elementary teachers using standardized measures of emotional intelligence, psychological need satisfaction, and stress and were analyzed using descriptive statistics, independent-samples t-tests, and Pearson product-moment correlation. Qualitative data were obtained through semi-structured interviews with five (5) purposively selected teachers and analyzed using thematic analysis to explore lived experiences, perceived stressors, coping strategies, support systems, and personal growth. Findings revealed a moderate level of emotional intelligence (M = 2.80), generally satisfactory fulfillment of psychological needs, and occasional experiences of stress (M = 3.09). Correlation analysis showed a significant positive relationship between emotional intelligence and psychological need satisfaction (r = .521, p < .001), while emotional intelligence (r = −.413, p < .001) and psychological need satisfaction (r = −.367, p < .001) were significantly and negatively associated with stress. Qualitative findings reinforced these results by demonstrating that emotional regulation, collegial and family support, acceptance, spirituality, and collaborative coping served as important protective mechanisms against work-related stress during crisis conditions.